The development of the psychologist's professional knowledge: a study of graduated in the UNLP, their insert in the educational field - Cardós, Paula Daniela (2009)
The studies on the formation of psychology's professors were locating us in the construction process of the professional knowledge in professors but in psychologists that exercise the teaching too, visualizing the paper that built knowledge assumed between both environments (academic and professional) and the relationship between them.